Management of Clinical Stage I Nonseminomatous Germ Cell Testicular Tumors: A 25-year Single-center Experience - Ondrusova, Martina; Waczulikova, Iveta; Lehotska, Viera; Zeleny, Tomas; Ondruš, Dalibor (Clinical genitourinary cancer, 2017)
BACKGROUND: Surveillance after orchiectomy alone has become popular in the management of clinical stage I nonseminomatous germ cell testicular tumors (CSI NSGCTT). Efforts to identify patients at high risk of disease progression led to a search for risk factors in CSI NSGCTT. The aim of this study was to analyze a 25-year single-center experience with risk-adapted therapeutic approaches-active surveillance (AS) versus adjuvant chemotherapy (ACT). PATIENTS AND METHODS: From January 1992 to January 2017, a total of 485 patients with CSI NSGCTT were stratified into the AS group (low-risk patients) and the ACT group (high-risk patients). Differences between relapse rates and overall survival rates in these groups were statistically analyzed. RESULTS: In the AS group, relapse occurred in 52 (17.3%) of 301 patients with a median follow-up of 7.2 months (range, 2-86 months). Six (2.0%) patients of this group died, with a median follow-up of 34.3 months (range, 11-102 months). In the ACT group, relapse occurred in 2 (1.1%) of 184 patients with a median follow-up of 56.2 months (range, 42-70 months). One (0.54%) patient died at 139.4 months following orchiectomy. The relapse rate for the AS group was 16.7 times higher than that for the ACT group. The groups did not differ in overall survival. The 3-year overall survival of all patients with CSI NSGCTT was 99.1% (95% confidence interval, 97.7%-99.7%). Three of a total of 7 deaths occurred thereafter. CONCLUSIONS: The policy of AS is recommended only in patients with low-risk CSI NSGCTT.
Keywords: dospělí; Neoplasms, Germ Cell and Embryonal; Recurrence; Watchful Waiting; Adult; výsledek terapie; mladý dospělý; testikulární nádory; pozorné vyčkávání; adjuvantní chemoterapie; lidé; Survival Analysis; staging nádorů; recidiva; Testicular Neoplasms; Treatment Outcome; germinální a embryonální nádory; Male; Young Adult; Chemotherapy, Adjuvant; Disease Management; analýza přežití; mužské pohlaví; Neoplasm Staging; management nemoci; Humans